MODIFICATION OF GENOME OF GRAPEVINE VIRUS A - Gritsenko , D.A.; Deryabina , N.D.; Galiakparov , N.N. (Eurasian Journal of Applied Biotechnology, 2017)
Grapevine virus A belongs to the Vitivirus genus. Grapevine virus A is involved in the etiology of Kober stem grooving, a disease of the grapevine rugose wood complex. The grapevine virus A genome (7.4 kb) consists of five open reading frames. The ORF2 function is not currently investigated. We attempted to develop a vector, based on grapevine virus A by cloning the gene encoding the capsid protein of apple chlorotic leaf spot virus in ORF2. Modification of grapevine virus A genome has not affected amplification or movement of virus through the plant. Symptoms of infection were detected 6-7 day after agroinfiltration. Nevertheless, immunoblotting has not detected the capsid protein of the capsid protein of apple chlorotic leaf spot virus either in the infiltrated leaves or in the upper leaves on the 15th day after agroinfiltration. It may be explained by the weak subgenomic ORF2 promoter. In addition, the genetic stability of modified grapevine virus A after K gene insertion was confirmed.